Knowledge of Delirium Among ICU Nursing Staff: A Cross-sectional Study - Chikku Mathew; Anju V. Ashok; Varghese P. Punnoose (Indian Journal of Psychological Medicine)
Background: Delirium is a reversible state that, if ignored, can result in increased morbidity and mortality. Studies from across the world have shown that nurses’ knowledge regarding delirium is inadequate. This study is one of the very few Indian studies addressing this issue. The study aims to infer an intensive care unit (ICU) nurse’s knowledge regarding delirium. Materials and Methods: This is a descriptive study carried out in the ICUs of a multispecialty general hospital. A convenient sample of 220 nurses was recruited after obtaining written informed consent. Knowledge regarding delirium was ascertained using the Delirium Knowledge Questionnaire; this, along with the sociodemographic variables, was circulated as Google Forms through WhatsApp groups. Data were analyzed using Statistical Package for the Social Sciences (SPSS) version 26, and results were presented as means and percentages. Results: The present study reveals that out of 211 nurses 130 (61.6%) had an average knowledge about delirium. Out of the 211 nurses 108 (51.2%) had average knowledge about clinical features of delirium and 105(49.8%) had average knowledge about etiology of delirium. More than half of the nurses (53.1%) had awareness regarding the medical management of delirium. In the domain of knowledge regarding non-medical management, 81 (38.4%) had excellent knowledge and 114 (54%) respondents had average knowledge regarding the prevention of delirium. Conclusion: The study calls for the need to provide educational interventions to the nursing staff for prevention, prompt recognition, and treatment of delirium.